Global Issues for Global Citizens : An Introduction to Key Development Challenges - Bhargava, Vinay (Washington, DC: World Bank, 2012)
This book grew out of the Global Issues seminars and is itself a testament to that two-way dialogue: the suggestion to compile the speakers' lecture notes into a book came from the students themselves. Both the seminars and this book reflect the Bank's conviction that the seemingly intractable problems of our globalizing world-from entrenched poverty, to climate change, to new infectious diseases such as AIDS and avian flu-can be solved, but only with the informed participation of a global citizenry, cooperating toward global solutions through global institutions that they themselves own. In today's world, the unchecked spread of disease. We are all called, as responsible global citizens, to inform ourselves about these issues, to then inform others, and finally to get involved in seeking solutions. One lesson that emerges from the book is that the global issues are very often interconnected, even if they may not seem so at first. The book also reminds us that many global issues derive from the undersupply of global public goods. The objective of this paper is to promote an understanding of key global issues and why they matter, to analyze the forces shaping public and private actions to address these issues, and to highlight the international actions that are being taken to address the global issues.